2015
DOI: 10.1002/mbo3.248
|View full text |Cite
|
Sign up to set email alerts
|

The antifungal plant defensin AhPDF1.1b is a beneficial factor involved in adaptive response to zinc overload when it is expressed in yeast cells

Abstract: Antimicrobial peptides represent an expanding family of peptides involved in innate immunity of many living organisms. They show an amazing diversity in their sequence, structure, and mechanism of action. Among them, plant defensins are renowned for their antifungal activity but various side activities have also been described. Usually, a new biological role is reported along with the discovery of a new defensin and it is thus not clear if this multifunctionality exists at the family level or at the peptide le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 50 publications
0
11
0
1
Order By: Relevance
“…Research over the past few decades revealed several functions of these molecules; for example, human defensin 5 (HD5) have Zn/Cd binding activity (Zhang et al, 2013). Other studies have shown that plant defensin gene type 1 (PDF1s) increases tolerance to zinc in yeast and plants (Mirouze et al, 2006;Shahzad et al, 2013;Nguyen et al, 2014;Mith et al, 2015). In addition, Cd stress was reported to significantly induce the expression of PDF1.2 in Arabidopsis, whereas Zn supply decreased its expression in a Zn/Cd hyperaccumulator, Noccaea caerulescens (Cabot et al, 2013;Gallego et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Research over the past few decades revealed several functions of these molecules; for example, human defensin 5 (HD5) have Zn/Cd binding activity (Zhang et al, 2013). Other studies have shown that plant defensin gene type 1 (PDF1s) increases tolerance to zinc in yeast and plants (Mirouze et al, 2006;Shahzad et al, 2013;Nguyen et al, 2014;Mith et al, 2015). In addition, Cd stress was reported to significantly induce the expression of PDF1.2 in Arabidopsis, whereas Zn supply decreased its expression in a Zn/Cd hyperaccumulator, Noccaea caerulescens (Cabot et al, 2013;Gallego et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…У мутанта SGECd t кадмий вызывал усиление экспрессии гена PI206, а также гена, кодирующего белок DRR230 (относящегося к растительным дефензинам), в побегах после суточной обработки растений кадмием. Дефензины, будучи большой группой антимикробных пептидов растений, принимают участие в основном в ответе на биотические стимулы, однако для небольшого числа дефензинов описано участие в процессах адаптации растений к абиотическим воздействиям, таким как холод [29][30][31], засоление [32,33], действие металлов [34][35][36][37]. Стоит отметить, что в корнях контрольных растений уровень экспрессии генов, кодирующих глутатионредуктазу и белки PrP4A и DRR230 усилен у мутанта SGECd t по сравнению с таковым у линии SGE.…”
Section: Discussionunclassified
“…Most natural plant AMPs are encoded by specific genes that are constitutively expressed at basal levels and are rapidly transcribed after being induced by pathogens. In response to pathogen stimulation, multiple AMPs can be found simultaneously in different organs of the same plant (Mith et al 2015 ). Most AMPs can target pathogens in a nonspecific way, and pathogens do not easily develop resistance to AMPs, which makes AMPs very suitable for developing plant disease resistance; the ability of AMPs to fight pathogens has been demonstrated by the expression of heterologous plant AMPs in transgenic plants (Goyal and Mattoo 2014 ).…”
Section: Application Potential Of Plant Ampsmentioning
confidence: 99%